Gut Microbiota Differs Between Parkinson’s Disease Patients and Healthy Controls in Northeast China - Li, Chunxiao; Cui, Li; Yang, Yimin; Miao, Jing; Zhao, Xiuzhen; Zhang, Jingdian; Cui, Guohong; Zhang, Ying (Frontiers in Molecular Neuroscience, 2019)
Background: There is accumulating evidence suggesting a connection between the gut and Parkinson’s disease (PD). Gut microbiota may play an important role in the intestinal lesions in PD patients. Objective: This study aims to determine whether gut microbiota differs between PD patients and healthy controls in Northeast of China, and to identify the factors that influence the changes in the gut microbiota. Methods: We enrolled 51 PD patients and 48 healthy controls in this study. Microbial species in stool samples were determined through 16S-rRNA gene sequencing. Dietary intakes were collected from subset of 42 patients and 23 controls using a food frequency questionnaire (FFQ). Gut microbiota species richness, diversity, differential abundance of individual taxa between PD patients and controls, and the relationship between the gut microbiota abundance and the dietary and clinical factors were analyzed. Results: PD patients showed decreased species richness, phylogenetic diversity, β-diversity, and altered relative abundance in several taxa compared to the controls. PD-associated clinical scores appeared to be the most influential factors that correlated with the abundance of a variety of taxa. The most consistent findings suggested by multiple analyses used in this study were the increase of Akkermansia and the decrease of Lactobacillus in PD patients in Northeast China. Conclusion: Gut microbiota significantly differed between a group of PD patients and healthy controls in Northeast China, with decreased species richness, phylogenetic diversity, β-diversity, and altered relative abundance in several taxa compared to the controls.